The Maatschap Paradox: Unpacking the Determinants of Slow Innovation Adoption among Indonesian Notaries - Rosita Yuwanasari; Pande Made Kutanegara; Dewi Haryani Susilastuti; Ninik Darmini (Journal of World Science, 2025)
The dominant practice of independent notaries in Indonesia is systematically vulnerable, causing service disruptions and losses for clients when a notary is unable to perform their duties. Although a superior alternative model, namely civil partnerships (maatschap), has a legal basis, its adoption rate is very low. This failure to innovate creates a market gap that is exploited by illegal actors and erodes public trust. Therefore, through a qualitative approach with a multi-site case study design, this article aims to uncover the root causes of this paradox and formulate policy recommendations to encourage professional transformation. The overall results of the study show that strong resistance to the adoption of maatschap is caused by a complex interaction between high-risk perceptions (especially loss of autonomy), a significant deficit of trust among peers, and the pressure of individualistic professional cultural norms. Four main determinants were identified as barriers: (1) ambiguous and unsupportive regulations, creating legal uncertainty; (2) low capacity for collaboration due to difficulties in building trust and a shared vision; (3) the complexity of technology management and integration; and (4) the failure of the socialisation process in building legitimacy and instilling new norms within the professional community.